Real-World Clinical, Psychosocial, and Economic Burden of Atopic Dermatitis: Results From the ESSENTIAL AD Multicountry Study - Spyridon Gkalpakiotis; Susanna Kannenberg; Külli Kingo; Hanan Rabea Nada; Margarita R. Rakhmatulina; Aleksandra Lesiak; Alin C. Nicolescu; Razvigor Darlenski; Alaa Masri; Limei Zhou; Teotonio Albuquerque; Shereen Hammad; et al. (Adis, Springer Healthcare, 2024)
Abstract Introduction Limited real-world evidence exists about the burden of atopic dermatitis (AD) in patients receiving systemic or non-systemic therapies in clinical practices. ESSENTIAL AD was an observational study that aimed to fill this information gap. Methods ESSENTIAL AD enrolled (September 2021-June 2022) adult patients with physician-confirmed AD that was routinely managed with systemic and non-systemic treatment in a real-world setting from 15 countries in Eastern Europe, the Middle East, and Africa. Primary outcome variables were Eczema Area and Severity Index (EASI), SCORing Atopic Dermatitis (SCORAD), and Dermatology Life Quality Index (DLQI) assessed during one office visit. Results A total of 799 enrolled patients fulfilled selection criteria and were included in the study. Patients mean (standard deviation [SD]) age was 36.3 (14.4) years, 457 (57.2%) were female, and the majority of patients were white (647 [81.0%]). Mean (SD) time since AD diagnosis was 17.6 (15.2) years (median 16.5; interquartile range [IQR] 3.3-26.8). The mean (SD) EASI, SCORAD, and DLQI total scores were 11.3 (11.3 [median 8.1; IQR 3.6-15.8]), 37.8 (17.9 [median 35.5; IQR 24.2-49.0]), and 10.6 (7.2 [median 10.0; IQR 5.0-15.0]), respectively. Patients receiving systemic treatment had significantly higher disease burden (mean [SD] EASI 13.3 [13.0]; median [IQR] 9.6 [3.9-17.9]) versus non-systemic treatment (mean [SD] 9.3 [8.7]; median [IQR] 6.8 [3.0-13.2]; P < 0.0001). Results were similar for SCORAD (39.9 [19.6] vs 35.6 [15.7]; median [IQR] 38.6 [24.7-53.1] vs 32.6 [23.9-44.6]; P = 0.0017), and DLQI total scores (11.4 [7.4] vs 9.9 [6.9]; median [IQR] 11.0 [5.0-16.0] vs 9.0 [5.0-14.0]; P = 0.0033, respectively). Conclusion Patients with AD continue to have substantial disease burden despite treatment with systemic therapy, suggesting that a need for effective disease management remains, including effective therapies that improve psychological outcomes and reduce economic burden of AD, in Eastern Europe, the Middle East, and Africa.